High-temperature air channel testing of thermally bonded PVC geomembrane seams. Issue 2 (April 2011) - Stark, T.D.; Pazmino, L.F.
Abstract : ABSTRACT: The objective of this paper is to present a procedure for high sheet temperature air channel testing of dual-track thermal seams for 0.75 mm thick polyvinyl chloride (PVC) geomembranes. This objective is accomplished by developing relationships between seam peel strength and seam burst pressure for sheet temperatures ranging from 46.7°C to 62.8°C during field air channel testing. This paper extends the original relationships presented by Thomas et al. and Stark et al., which extend only to 46.7°C, because a sheet temperature greater than 46.7°C is frequently encountered during hot summer months. The original relationship is extended to 62.8°C using the Arrhenius model, and a polynomial equation is presented that can be used to convert the sheet temperature during field air channel testing to the air channel pressure required to ensure that the specified seam peel strength of 2.6 N/mm is met or exceeded. Thus the proposed relationship and equation allow the seam peel strength to be verified by field air channel testing without conducting destructive tests.